ESTIMASI EROSI DI DAERAH ALIRAN SUNGAI (DAS) BODRI MENGGUNAKAN METODE UNIVERSAL SOIL LOSS EQUATION (USLE) - Islami, Qonitath Bella; Setyaningsih, Wahyu; Suroso, Suroso (Geo-Image, 2017)
The amount of sedimentation in downstream watersheds can be affected by inappropriate land use in upstream watersheds. This inappropriate use of land can lead to erosion in the Bodri watershed. The purpose of this study was to calculate the amount of erosion in the Bodri watershed using the USLE method. The variables used in this research are rain erosivity factor (R), soil erodibility factor (K), long factor and slope (LS), plant management factor (C), conservation action factor (P). Data collection techniques used include documentation, image interpretation and observation. Rainfall data processing using erosivity formula, soil erodibility, slope length and slope, crop management and conservation action using comparative technique with reference table. The amount of erosion (E) is calculated using the USLE formula, E = RxKxLSxCxP using map overlay technique. The result of this research is the average annual erosion of Bodri Watershed of 169.47 ton / ha / yr with the average annual erosion value from highest to lowest respectively, that is Putih watershed, Logung watershed, Lutut watershed and Bodri Hilir watershed with respectively 282,118 ton/ha year, 262,394 ton/ha/year, 144,193 ton/ha/year and 99,397 ton/ha/year. These results indicate that the Putih watershed contributes greatly to the erosion occurring in the Bodri watershed.